Impact of Preoperative CT-Measured Sarcopenia on Clinical, Pathological, and Oncological Outcomes After Elective Rectal Cancer Surgery - David Martin; Mathilde Billy; Fabio Becce; Damien Maier; Michael Schneider; Clarisse Dromain; Dieter Hahnloser; Martin Hübner; Fabian Grass (Diagnostics)
Background: Patients with rectal cancer may be exposed to a loss of muscle strength and quality. This study aimed to assess the role of preoperative CT-based sarcopenia on postoperative clinical, pathological, and oncological outcomes after rectal cancer surgery. Methods: This retrospective monocentric study included patients who underwent elective oncologic resection for rectal adenocarcinoma between 01/2014 and 03/2022. The skeletal muscle index (SMI) was measured using CT at the third lumbar vertebral level, and sarcopenia was defined based on pre-established sex-specific cut-offs. Patients with sarcopenia were compared to those without sarcopenia in terms of outcomes. A Cox proportional hazard regression analysis was used to determine the independent prognostic factors of disease-free survival (DFS) and overall survival (OS). Results: A total of 208 patients were included, and 123 (59%) had preoperative sarcopenia. Patients with sarcopenia were significantly older (66 vs. 61 years, p = 0.003), had lower BMI (24 vs. 28 kg/m2, p < 0.001), and were mainly men (76 vs. 48%, p < 0.001). There was no difference in overall and major complication rates between the sarcopenia and non-sarcopenia group (43 vs. 37%, p = 0.389, and 17 vs. 17%, p = 1.000, respectively). Preoperative and postoperative features related to rectal surgery were comparable. The only predictive factor impacting OS was R1/R2 resection (HR 4.915, 95% CI, 1.141–11.282, p < 0.001), while sarcopenia (HR 2.013, 95% CI 0.972–4.173, p = 0.050) and T3/T4 status (HR 2.108, 95% CI 1.058–4.203, p = 0.034) were independently associated with DFS. Conclusions: A majority of patients undergoing rectal cancer surgery had preoperative CT-based sarcopenia. In this cohort, sarcopenia had no impact on postoperative morbidity and OS but was independently associated with DFS.